Predictors of Illness Severity in COVID-19 Cases in Saudi Arabia - Al Dossary R (Infection and Drug Resistance, 2021)
Reem Al Dossary,1 Amani Alnimr,1 Reem Aljindan,1 Khaled R Alkharsah,1 Ahmed K Al-Qurayn,1 Obeid Eltreifi,1 Feras A Alkuwaiti,2 Abdullah B Almashouf,2 Ahmed M Alsahlawi,2 Amal Alshammari,3 Dhoha Hudhaiah,3 Mohammed S Alshahrani,4 Huda Bukhari2 1Department of Microbiology, College of Medicine, Imam Abdulrahman bin Faisal University (IAU), Dammam, Saudi Arabia; 2Department of Internal Medicine, College of Medicine, Imam Abdulrahman bin Faisal University (IAU), Dammam, Saudi Arabia; 3Department of Medical Laboratory, King Fahd Hospital of the University, Imam Abdulrahman bin Faisal University (IAU), Dammam, Saudi Arabia; 4Department of Emergency Medicine, King Fahd Hospital of the University, Imam Abdulrahman bin Faisal University (IAU), Dammam, Saudi ArabiaCorrespondence: Reem Al Dossary P.O Box: 1982, Dammam, 34221 Tel +966 333 0000 ext 35155Email raaldossary@iau.edu.saPurpose: Multiple studies worldwide have reported the clinical and epidemiological features of coronavirus disease 2019 (COVID-19), with limited reports from the Middle East. This study describes the clinical and epidemiological features of COVID-19 cases in the Eastern Province of Saudi Arabia and identified factors associated with the severity of illness.Patients and Methods: This was an observational study of 341 COVID-19 cases. These cases were reported in the first three months after the first case in the country was identified. Clinical and demographic data were analyzed and described to identify the effects of age, sex, and ethnicity on illness severity. In addition, the duration of viral shedding and cycle threshold (Ct) values of real-time PCR were evaluated as predictors of severity.Results: The median age was 45 years. Males were twice as likely to be infected than females (p < 0.0001). The duration of viral shedding ranged from 9 to 36 days. The most common clinical presentations include fever, shortness of breath, cough, myalgia, sore throat, vomiting, and headache. Critical cases were significantly higher in men (23% vs 8.7%), senior adults (> 65 years), individuals of Bengali ethnicity, and in patients with comorbidities including diabetes, hypertension, and dyslipidemia (p =0.001). The case fatality rate was found to be 10%. The fatality was significantly higher in males than females (13.8% vs 2.6%), and in Asians (17.9%) than Arabs (6%) and Africans (0) (p =0.002). No association was found between viral load, represented by the RT-PCR cycle threshold (Ct) values, and severity of illness.Conclusion: Age, sex, and ethnicity are important predictors of COVID-19 severity. The cycle threshold (Ct) of the SARS-CoV-2 RT-PCR test cannot be used as a predictor of the criticality of illness.Keywords: factors, ethnicity, Ct value, Arabs, virus shedding